2019
DOI: 10.1101/555771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of sex on the urogenital microbiome of rhesus monkeys

Abstract: 14The vaginal microbiome of nonhuman primates (NHPs) differs substantially from humans 15 in terms of Lactobacillus abundance, overall taxonomic diversity, and vaginal pH. Given 16 these differences, it remains unclear in what way the NHP genital microbiome protects 17 against pathogens, in particular sexually transmitted diseases. Considering the effect that 18 microbiome variations can have on disease acquisition and outcome, we examined 19 endogenous and exogenous factors that influence the urogenital micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…In the experiment conducted, primiparous ewes had significantly higher levels of the tested phyla than ewes in the second parity. Studies conducted in recent years suggest that the composition of the microbiome may also be influenced by hormones, particularly sex hormones [ 21 , 22 ]. In a study conducted by Markle et al [ 23 ] on mice, it was demonstrated that there is a direct interaction between sex hormones and the gastrointestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experiment conducted, primiparous ewes had significantly higher levels of the tested phyla than ewes in the second parity. Studies conducted in recent years suggest that the composition of the microbiome may also be influenced by hormones, particularly sex hormones [ 21 , 22 ]. In a study conducted by Markle et al [ 23 ] on mice, it was demonstrated that there is a direct interaction between sex hormones and the gastrointestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…They are responsible for the maturation of the genital organs or the formation of secondary sexual characteristics. They also affect many metabolic pathways, including lipid metabolism, inhibition of gastrointestinal motility, and have an indirect effect on intestinal absorption, which is associated with the gastrointestinal microbiome [ 22 , 24 , 25 ]. Additionally, the study by Menon et al [ 26 ] indicates that sex hormone levels may be important in gastrointestinal tract microbial variation.…”
Section: Discussionmentioning
confidence: 99%
“…ciąża czy ruja, a także różnice w poziomie niektórych hormonów. Czynniki te często zróżnicowane są ze względu na płeć [70,[74][75][76]. W badaniach przeprowadzonych na myszach w okresie ciąży wykazano, że w przypadku samic dochodzi do zmniejszenia wrażliwości na insulinę, a także zmienia się ich mikrobiom, przygotowując je na gromadzenie zapasów energetycznych na okres odchowu potomstwa.…”
Section: Czynniki Biologiczne I Genetyczneunclassified